KANDUNGAN SENYAWA KIMIA DAN AKTIVITAS FARMAKOLOGI TANAMAN MATOA (Pometia Pinnata J.R. Forster & J.G. Forster) - Rahmawati, Rahmawati; Tahir, Masdiana; Amir, A. Hesti Wulandasari (As-Syifaa Jurnal Farmasi, 2021)
Island lychee (Pometia pinnata J.R.Forster & J.G.Forster) is a plant species from the Sapidaecae family used as a medical plant that plays a role in healing or improving health condition of the community. This research aimed to determine the content of chemicah compound and pharmacologycal activity of several types of island lychee extract. The review on the study of the chemical content and pharmacologycal activity of island lychee was conducted by searching the literature related to chemical and pharmacologyal review accessed on several journal provide sites (google scholar). Then it was proceeded with screening on these journal to obtain sources that fall with in the inclution criteria. Island lychee has many properties that have been scientifically proven. Several types of the extract are reported to have pharmacologycal activity that can be develop as antioxidans, antibacterials, antimicrobials, antiperusemia, antihyperglycemic/antidiabetic, anticancer and diuretic. The pharmacologycal activity is due to the compound group of alkaloids, flavonoids, phenols, coumarin, polyphenol, saponin, steroids, tannins and terpenoids